Socialization of Balanced Nutrition with Comic Media and Assistance for Urban Gardening in Waiheru Village - Khartini Kaluku; Martha Puspita Sari*; Yeni Fikasari (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
Basic Health Research data from the Ministry of Health of the Republic of Indonesia in 2018 showed that nationally the problem of central obesity at the age of 15 years was still serious, namely, 31%, while the prevalence of central obesity at the age of 15 years in Maluku reached 33%. Obesity is becoming a health problem worldwide; even the WHO states that obesity has become a global epidemic. Obesity is a health problem that must address immediately because it is a risk factor for degenerative diseases and metabolic syndrome. Obesity in adolescents needs to get serious attention, be consistent, and be addressed together. To improve health status and optimize adolescent growth and development, it is necessary to apply a healthy diet through the socialization of balanced nutrition with comic media and implementation assistance. Urban gardening for teenagers through mosque youth can be an effort to implement healthy eating patterns for teenagers for optimal nutrition and health status.